Screen Choice: The Relations, Interactions and Articulations of Watching Film. Issue 1 (7th June 2021) - Hanchard, Matthew; Merrington, Peter; Wessels, Bridgette
Abstract : People watch films on televisions, laptops, tablets, smartphones, and cinema screens. As technologies, each of these screen types provide different opportunities to select particular films, and to choose when and where to watch them. This raises questions about how and why people choose particular screens and the viewing experiences they gain from doing so. To address these questions, we draw on 200 semi-structured interviews with film audience members in England. We use Livingstone's (1998, 2013 ) notion of interactions and relations and Hartmann's (2006 ) notion of a 'triple articulation' of media to approach screens as technologies that carry a particular range of films. Here, films are understood as texts, and each screen a medium that provides opportunities to watch films in specific temporal and spatial contexts. We find that people tend to: (1) watch films at the cinema, either to socialise or to feel part of an temporary auditorium-based community – whilst immersing within the text; (2) on television sets in the living-room to relax or socialise; (3) on laptops or tablets in the bedroom for personalised engagement; and (4) via smartphones for convenience and to pass time when away from home. Overall, we argue that people's film-watching is embedded within specific contexts and that people choose particular screen types for the opportunities they offer for watching particular films in particular times and places. In this, people choose screen types and configure various temporal and spatial aspects of their film-watching environments to seek out specific viewing experiences.